Mapping 'Chinese' Christian Schools in Indonesia: Ethnicity, Class and Religion - HOON, Chang Yau (Institutional Knowledge at Singapore Management University, 2010)
Schools are not ‘‘innocent’’ sites of cultural transmission. They play an active and significant role in transmitting values and inculcating culture. Schools also serve as a site for the maintenance of boundaries and for the construction of identities. Previous studies have recognized the relationship between education and identity. Building on existing literature, this study examines the ways in which Christian schools can be a site for the construction and maintenance of religious, ethnic and class identities of the ethnic Chinese in Indonesia. The study surveys four prestigious ‘‘Chinese’’ Christian schools in Jakarta. Through a brief but thorough profiling of the schools, the study explores the complexity of and identifies issues associated to religion, ethnicity and class, in relations to Chinese-Indonesians and the Indonesian society at large.